Modeling human telencephalic development and autism-associated SHANK3 deficiency using organoids generated from single neural rosettes - Yueqi Wang; Simone Chiola; Guang Yang; Chad Russell; Celeste J. Armstrong; Yuanyuan Wu; Jay Spampanato; Paisley Tarboton; H. M. Arif Ullah; Nicolas U. Edgar; Amelia N. Chang; David A. Harmin; et al. (Nature Communications, 2022)
Our understanding of human brain development in health and disease is limited. The authors generated human brain organoids from stem cell-derived isolated single neural rosettes to study human cortico-striatal development and deficits caused by an autism-associated genetic abnormality in SHANK3.